Analisis Peran Guru dan Orang Tua dalam Penguatan Literasi Digital Peserta Didik di Masa Pascapandemi Covid-19 - Azhari, Suci Putriani; Ulfah, Suci Nurmaya; Darfila, Wa Ode Siti; Lessy, Zulkipli (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2023)
The recent Covid-19 Pandemic has further institutionalised the applications of digital technologies in education. Some schools are not ready to do a distance learning class because of the limited ability of teachers and parents to use technology. Meanwhile, after covid-19 pandemic, there were many students whose moral decreased. This study aims to describe and determine how the role of teachers and the role of parents to strengthening of digital literacy in post-pandemic era. The research approach used is descriptive qualitative in the nature of field research located at UPTD SD Negeri 13 Perupuk, Lima Puluh Pesisir, Batubara. Informants in this research were head of school, teachers, and parents. While the data collection used through interviews that had been conducted to be strengthened and corrected. The data analysis techniques are data reduction, data presentation, and verification or drawing conclusions. The findings show the role of the teachers and parents both are very important to strengthening of digital literacy their children. The findings show that the students at SDN 13 Perupuk accept the use of gadgets due to their usefulness and easiness. However, there were some negative impacts of gadget usage in terms of social life and whose moral decreased. Therefore, teachers and parents must giving guidance to students in using digital technologies in education